Normal pubertal development in a female with carbohydrate deficient glycoprotein syndrome. Issue 3 (March 1996) - Pineda, M; Pavia, C; Vilaseca, M A; Ferrer, I; Temudo, T; Chabas, A; Stibler, H; Jaeken, J
Abstract : A girl is reported who presented with many of the clinical and biochemical characteristics of type I carbohydrate deficient glycoprotein syndrome. Unusually, however, she experienced a normal pubertal development.